Genetically predicted inflammatory proteins and the risk of atrial fibrillation: a bidirectional Mendelian randomization study - Ma, Zhiqiang; Chen, Qiao; Liu, Ziyuan; Li, Xueyu; Zhang, Huaming; Feng, Xi (Frontiers in Cardiovascular Medicine, 2024)
The causal associations between inflammatory factors and atrial fibrillation (AF) remained unclear. We aimed to investigate whether genetically predicted inflammatory proteins are related to the risk of AF, and vice versa.A bidirectional two-sample Mendelian randomization study was performed.The genetic variation of 91 inflammatory proteins were derived from genome-wide association study (GWAS) data of European ancestry (n =14,824). Summary statistics for AF were obtained from a published meta-analysis study (n =1,030,836) and the FinnGen study (n =261,395).Results: Genetically predicted fibroblast growth factor 5 (FGF5) was significantly positively associated with risk of AF [(odds ratio (OR): 1.07; 95% CI: 1.04 -1.10; P < 0.01), and CD40L receptor was significantly negatively associated with risk of AF (OR: 0.95; 95% CI: 0.92 -0.98; P = 0.02) in the meta-analysis study. In the FinnGen study, similar results were observed in FGF5 (OR: 1.11; 95% CI: 1.06 -1.16; P < 0.01) and CD40L receptor (OR: 0.93; 95% CI: 0.89 -0.97; P = 0.03) for AF. In the FinnGen study, TNF-beta was significantly positively associated with risk of AF (OR: 1.05; 95% CI: 1.02 -1.09; P = 0.03) and leukemia inhibitory factor receptor was significantly negatively associated with risk of AF (OR: 0.86; 95% CI: 0.80 -0.91; P = 0.001). The causal effect of AF on inflammatory proteins was not observed.Our study suggested that FGF5 and CD40L receptor have a potential causal association with AF, and targeting these factors may help in the treatment of AF.